A core-equilibrium convergence in an economy with public goods - Nizar Allouch (Queen Mary University of London, Department of Economics, 2009)
This paper deals with a core-equilibrium equivalence in an economy with public goods where preferences of consumers display warm glow effects. We demonstrate that provided that each consumer becomes satiated to other consumers provision, it holds that, for a sufficiently large economy, the set of Edgeworth allocations is non-empty. Moreover, we show that an Edgeworth allocation could be decentralized as a warm glow equilibrium.
Keywords: H41; C71; D64; 330; competitive equilibrium; warm glow; public goods; Edgeworth; core; decentralization; Gleichgewichtstheorie; Öffentliches Gut; Altruismus; Wohlfahrtstheorie; Core; Dezentralisierung; Theorie